Aesthetics and politics - Adorno, Theodor; Benjamin, Walter; Bloch, Ernst; Brech, Bertolt; Lukacs, Georg; Jameson, Fredric (London ; New York : Verso, 2007)
In 'Aesthetics and Politics' the key texts of the great Marxist controversies over literature and art are assembled in a single volume. They do not form a disparate collection but a continuous, interlinked debate between thinkers who have become giants of twentieth-century intellectual history.
Discussing expressionism / Ernst Bloch -- Realism in the balance / Georg Lukacs -- Against Georg Lukacs / Bertolt Brecht -- Conversations with Brecht / Walter Benjamin -- Letters to Walter Benjamin / Theodor Adorno -- Reply / Walter Benjamin -- Reconciliation under duress / Theodor Adorno -- Commitment / Theodor Adorno -- Reflections in conclusion / Fredric Jameson.
This translation originally published: London: NLB, 1977.
Includes bibliographical references and index.
ENH
Trim Education
Text in English, translated from the German.
Keywords: Aesthetics; Communism and philosophy -- Germany; Estetica comunista